Salmonella isolated from street foods and environment of an urban park: A whole genome sequencing approach - Christian Vinueza-Burgos; José Medina-Santana; Maria Ishida; Brian Sauders; Gregory Deiulio; Alyssa Dickey; Pablo Endara; Rommy Terán (PLoS ONE, 2025)
Salmonella is one of the most important foodborne pathogens worldwide. Therefore, this study was conducted to understand the importance of this microorganism in street food and the environment of an urban park in Quito, Ecuador. This research included phenotypic characterization and whole genome sequencing (WGS) analysis of isolates from different food matrices and fecal samples of dogs and pigeons. Salmonella was found in 10% (18/180) of the food samples, 3% (3/100) of the dog stool samples, and 5% (5/100) of the pigeon stool samples. These results also showed that meals containing any sauce or eggs were associated with a high probability of Salmonella isolation, regardless of other ingredients. All Salmonella isolates from food were identified as Salmonella enterica serovar Typhimurium (S. Typhimurium) while isolates from animal feces belonged to Salmonella enterica serovar Infantis (S. Infantis) and S. Typhimurium. WGS analysis showed that all S. Typhimurium strains belonged to ST19 and S. Infantis to ST32 according to the Multi-Locus Sequence Type (MLST) scheme. These strains were not related to Salmonella genomes of other origins when a Single Nucleotide Polymorphism (SNP) tree analysis was carried out. Antimicrobial resistance genes, such as blaCTX-M-65, were predominantly linked to the pESI-like plasmid found in S. Infantis. These results show the importance of urban fauna as a reservoir of S. Infantis and the impact these animals could have in terms of public health.